La verdad biológica en el derecho a la identidad personal de niños, niñas y adolescentes en Ecuador - Navarro, Yadira E. (2021)
The Right to Personal Identity based on the principle of biological truth has become an important part in the structuring of the personal identity of children and adolescents because they are in a process of development. Ecuador recognizes in its 2008 constitution the Right to Personal Identity, which is why its state apparatus has the obligation to develop regulations aimed at its protection. However, it has become evident that there are actions that are not regulated and cause violation of the aforementioned right.